2014
DOI: 10.1080/03081079.2014.885512
|View full text |Cite
|
Sign up to set email alerts
|

Configuration complexity assessment of convergent supply chain systems

Abstract: System designers usually generate alternative configurations of supply chains (SCs) by varying especially fixed assets to satisfy a desired production scope and rate. Such alternatives often vary in associated costs and other facets including degrees of complexity. Hence, a measure of configuration complexity can be a tool for comparison and decisionmaking. This paper presents three approaches to assessment of configuration complexity and their applications to designing convergent SC systems. Presented approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…Firstly, the coding algorithm used to generate the feasible design space could be ineffective for network designs with a large number of suppliers. This is because the number of combinations of a supply network exponentially increases with the quantity of suppliers [23], [31]. Sophisticated clustering algorithms and meta-heuristics optimisation methods can be employed to offset the increased computational load within an acceptable time-frame.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Firstly, the coding algorithm used to generate the feasible design space could be ineffective for network designs with a large number of suppliers. This is because the number of combinations of a supply network exponentially increases with the quantity of suppliers [23], [31]. Sophisticated clustering algorithms and meta-heuristics optimisation methods can be employed to offset the increased computational load within an acceptable time-frame.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Wang et al [20] examined the impact of OCC on overall system throughput and found that variety-induced complexity can hinder the human cognitive efficiency and human reaction times in assembly operations, and hence affects the rework/scrap rate of assembly stations and disturbs assembly line throughput. Information entropy was also used alongside graph theory-based metrics (e.g., vertex degree) to quantify complexity in assembly supply chain networks [3], [21]- [23]. A summary of the literature review on supply chain complexity assessment is given in Table 1.…”
Section: Conceptual Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Pathak et al (2007) and Hearnshaw and Wilson (2013) highlighted that SCC and adaptation phenomena can be better managed through complex adaptive system (CAS) principles. For measuring the structural complexity of the supply chain, Modrak and Marton (2013, 2014) proposed a vertex degree index ( I vd ) adapted from Shannon’s theory of entropy. Elmaraghy et al (2014) proposed a layout complexity assessment index for measuring the structural complexity of manufacturing layout.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Subsequently, product design parameters are transformed into the production work order document determining the sequence of operations. An important feature of the system modularity is that complexity of technical systems can be effectively managed through their modular design [9][10][11][12]. Tate [13] categorized modularity from the Axiomatic Design theory perspective into three types: resource, operational, and interfacial.…”
Section: Introductionmentioning
confidence: 99%